Proposal of a Multimodal Interactive Architecture Based on a Social Indoor and Outdoor Navigation System - Silva, Heli Neres; Paulino, Emanuelle Gonçalves; Diaz-Amado, José; Lima, Crescencio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Technological advancements have spurred the development of social robotics, aiming to create service robots that can closely interact with humans. However, direct human-robot interaction presents challenges, particularly in terms of social behavior and adherence to social constraints. This work proposes a hybrid architecture for seamless navigation in indoor and outdoor environments, integrating harmoniously with society. The architecture contributes to the advancement of social robotics by enhancing human-robot interaction, improving quality of life, and opening new possibilities for technology utilization. It consists of five layers: Detection, Perception, Database, Planning and Decision-Making, and System Management, encompassing essential components or algorithms for autonomous system functioning. The expected outcome is improved interaction between service robots and humans through advanced perception capabilities, efficient route planning, and behavioral adaptation to social constraints. The architecture provides flexibility and scalability, enabling component replacement or modification without compromising system operation. The proposed hybrid architecture offers an organized and flexible structure for autonomous systems, facilitating efficient and safe human-robot interaction. By considering social and emotional aspects, it aims to enhance the interaction experience and foster harmonious collaboration. Future work involves implementing and testing the architecture in social robotic systems, utilizing the Robot Operating System (ROS) for module communication and potential software adjustments.